STUDENTS' PERCEPTIONS OF ONLINE LEARNING IN CRITICAL AND CREATIVE READING COURSES UMMY SOLOK - Mega Putri (Asosiasi dosen IDEBAHASA KEPRI, 2021)
This research was motivated by the Covid-19 pandemic which changed the order of life, including in the world of education. Online learning is a solution so that learning continues even with all its advantages and disadvantages. However, it needs adjustments both in terms of lecturers and students in its implementation. In the learning process, the main things that must exist include: teaching and learning process, competence of lecturers and facilities and infrastructure. The purpose of this study was to analyze students' perceptions of online learning in the Critical and Creative Reading course at UMMY Solok. This type of research is survey research. The data collection technique is in the form of a questionnaire, the questionnaire used is a closed questionnaire type in the form of a rating scale, namely a questionnaire that has available answers, then analyzed using descriptive statistics. The results of this study explain that the learning process is categorized as good, lecturer competence is in good category, and facilities and infrastructure are in sufficient category. From the results, it can be concluded that in online learning the teaching and learning process has been going well and the competence of lecturers in providing learning is also good even though the facilities and infrastructure are still lacking. Improvements are needed not only in terms of students and lecturers but also the campus.